La comprensión de textos narrativos en estudiantes del sexto grado de educación primaria en la Institución Educativa N°60756 Claverito, Iquitos 2021 - Chumbe Flores, Ninfa Otilia (2022)
The objective of this research was to describe the level of achievement of the comprehension of narrative texts in the students of the sixth grade of primary education of the Educational Institution No. 60756 Claverito, Iquitos, 2021. It has a quantitative and descriptive approach. The simple descriptive design Ox, and was used. The population consisted of 140 students. The sample was 80 students, 20 for each sixth grade section. To measure the level of achievement of narrative text comprehension, the questionnaire instrument was used. The results obtained indicate that "The level of achievement of the comprehension of narrative texts is at the beginning in the majority of the students (43.8%) of the sixth grade of primary education of the Educational Institution No. 60756 Claverito, Iquitos, 2021, and they reach an average of 10.8 points. Regarding the literal, inferential and critical dimensions, in the first they reach a passing average of 12.2, in the last two the average is disapproving: 9.65 and 10.65 respectively. It is concluded that the learning of the comprehension of narrative texts is not developed at acceptable levels in the students of the sixth grade of primary school.